Impacto de la contribución solidaria sobre utilidades en los resultados del ejercicio 2016 de la empresa Ferretol cia. ltda. del sector Colaisa del cantón Latacunga - Álvarez Plazarte, Rosa Angélica (2017)
This project focused on the impact generated by the solidarity contribution on profits in the results of the year 2016 at Ferretol Cía. Ltda. in Colaisa sector, Latacunga Canton because the earthquake that occurred on April 16th, 2016; due to this catastrophe, the biggest problem detected in this enterprise was in its planning there were no provisions of any value for fortuitous cases, due to this, what is being identified with this research project is the impact that this contribution caused on the results of the fiscal year 2016; also, it was determined that 10.61% of the total expenses represented the solidarity contribution, the calculation was made based on the results of 2015, and the amount established had to be canceled in three equal installments in the months of June, July and August of the year 2016. This type of research is closely linked with the solidarity contribution on profits; its main objective is to determine how financially affect the company, through a previous analysis of the financial statements of 2016. Subsequently, for the development of this project has been used to descriptive methodology that allowed to describe past events and in this way helped to know the real situation of the company, as technique was used the interview to be able to perform it to the legal representative and the accountant of the company. Finally, based on the research, a simulation was made about the impact of the solidarity tax on profits in the months of June, July and August determining that the loss that the company had was not only the amount of the contribution but a higher value, since if this company had not contributed with this tax, it would have the possibility of obtaining more merchandise for sale; thus generating a higher profit which was presented when the company had to contribute.